Catalytic oxidation of CO on metals involving an ionic process in the presence of H2O: the role of promoting materials. Issue 2 (1st December 2014) - Tanaka, Ken-Ichi; He, Hong; Yuan, Youzhu
Abstract : A new catalytic oxidation of CO is enhanced by H2 O molecule on the Pt and Au with specific promoting materials where the rate-determining reaction of HCOO(a) + OH → CO2 + H2 O is promoted by repeated contribution of OH − anion via messenger molecule H2 O. Abstract : A new catalytic oxidation of CO involving an ionic process in the presence of H2 O is proposed on a Pt-catalyst with specific promoting materials (co-catalysts). Oxidation of CO is very slow at room temperature on ordinary Pt-catalysts such as Pt/SiO2, Pt/Al2 O3, Pt/TiO2, Pt/Graphite, and Pt/carbon nano-tube (CNT), and H2 or H2 O have no effect on the reaction. However, in the presence of specific co-catalysts, the oxidation of CO is markedly enhanced by H2 or H2 O, so that highly selective preferential oxidation (PROX) of CO in H2 is attained. The role that co-catalysts play in the oxidation of CO enhanced by H2 or H2 O was clarified by the experiments with Pt supported on CNT and carbon nano-fiber (CNF) that had Ni–MgO and FeO x at their one terminal end, respectively. Oxidation of CO was markedly enhanced by H2 on the Pt/CNT and Pt/CNF, but no enhancement was observed on the Pt/CNT-p and Pt/CNF-p, where the CNT-p and CNF-p were purified by removing Ni–MgO and FeO x . Similar enhancement of the oxidation of CO by H2 or H2 O was observed on FeO x /Pt/TiO2 and FeO x /Au/TiO2, although no enhancement was observed on the Pt/TiO2 and Au/TiO2 catalysts. The in situ DRIFT spectra of the FeO x /Pt/TiO2 catalyst (Fe : TiO2  : Pt = ca. 100 : 100 : 1) during reaction in a flow of (CO + O2 + H2 ) suggested the rate-determining slow step was HCOO(a) + OH(a) → CO2 + H2 O. The oxidation of CO enhanced by H2 O/D2 O and H2 /D2 showed a common hydrogen isotope effect of r H / r D = 1.4–1.5. The highly selective oxidation of CO in H2 on the Pt/CNT and Pt/CNF catalysts strongly suggests efficient transport of ionic intermediates from Ni–MgO or FeO x to Pt over the hydrophobic CNT and CNF surface according to the local potential gradient. According to this mechanism, selectivity in the preferential oxidation of CO in H2 is defined by the turnover number of a H2 O molecule forming CO2 during its residence time on the catalyst, which is essentially different from the selectivity based on competitive adsorption and/or reaction. The role of the H2 O molecule is as a kind of messenger molecule or a molecular catalyst to promote the reaction on the surface expressed by the equation n (CO + 1/2O2 ) + H2 O → n CO2 + H2 O. In this mechanism, the selectivity is given by n /( n + 1). Curious phenomena previously observed in the PROX reaction of CO in H2 on various catalysts are well explained by the mechanism including an ionic process proposed in this paper.